Corporate financial policy and investor taxation in Austria: An empirical investigation - Magdalena Haring; Rainer Niemann (Arbeitskreis Quantitative Steuerlehre (arqus), 2010)
The paper analyzes the impact of in investor capital gains taxation on corporate leverage of Austrian corporations. We conduct our analyses for a unique sample of Austrian firms, including a large part of non-listed corporations. By means of regression analyses we show that the capital gains tax rate, the fraction of taxable investors of a corporation as well as the dividend payout ratio are significant determinants of the financing decisions of Austrian firms. Legal status, listing and corporate profitability also affect the debt ratio of corporations in Austria. Additionally we show that family-owned companies behave differently from other corporations, indicating the importance of research on family businesses. Sensitivity analyses accounting for different calculations of the effective tax rate on capital gains show that our obtained results are robust.
Keywords: 330; Kapitalstruktur; Wertzuwachssteuer; Steuerbelastung; Finanzierung; Entscheidung; Schätzung; Österreich